Leaving Everything Most Loved : Maisie Dobbs #10 - Winspear, Jacqueline, 1955- (New York : Harper, 2013)
When the body of an Indian woman is found in a south London canal, Maisie Dobbs is asked to investigate by the victim's brother, a task that takes Maisie into a dangerous, and unexpected, exotic world.
Keywords: Dobbs, Maisie (Fictitious character) -- Fiction; Women private investigators -- England -- Fiction; Murder -- Investigation -- Fiction; Dobbs, Maisie (Fictional character) -- Fiction; Women detectives -- England -- Fiction; Homicide -- Fiction; Great Britain -- History -- George V, 1910-1936 -- Fiction; Great Britain -- History -- 20th century -- Fiction; Mystery fiction